Environmental policy and governance in China - Kitagawa, Hideki (Springer, 2017)
This book focuses on how to create an environmentally friendly society in China from the viewpoint of environmental law and policy. The authors accessed a great number of valuable sources not available in English, and interviewed various scholars and public officials, in order to analyze the environmental policies in China while comparing some of the features to Japan. The book stresses the importance of introducing a brand-new policy of central and local government, and analyses why these policies have not been executed effectively in the local society. In addition to the economy-oriented policy and spirit of the Chinese nation, which are the main causes, this book also highlights shortcomings in the inspection system, information management, and the extremely low degree of public participation as important aspects to focus on in order to tackle the current problems. The individual chapters will help readers to understand the environmental issues in China in depth, and provide guidance on resolving the issues in China and in developing countries that are now or soon will be facing the challenge of combining economic growth and environmental improvement. Air, water and soil pollution are serious challenges in China. The deterioration of the environment often leads to rioting that influences social stability, which is also a great concern to foreign investors. This book will be of interest to a professional audience such as policymakers, journalists, members of environmental NGOs, managers and employees who do business with China, as well as academic researchers and students.
Keywords: Environmental policy -- China.; China.; elektronické knihy; electronic books